AC-OP water filter - Andrew, Shirley Arvilla; Mohammad, Siti Aminah; Nor Azmi, Nor Faranaz Shamin; Lepit, Ajis (Universiti Teknologi MARA, Kedah, 2023)
Water is the source of life which is an invaluable natural treasure for all living organisms on Earth. Water is essential for residential, commercial, industrial, and agricultural consumers worldwide. Water was originally clean but the cleanliness and quality of water began to be contaminated due to human activities. Contaminated water can cause damage to the ecosystem and the sustainability of nature and even threaten human life because polluted water can cause various diseases. Globally, consumers not only confronted the water issue on the quality of water but also on the insufficient sources of clean water. Malaysia is the second largest exporter of palm oil in the world thus produces abundant of palm oil waste. Consequently, this project aims to explore the potential of activated carbon produced from empty fruit bunch (EFB) of palm oil waste as a water filter. The name of the innovation is AC-OP water filter which named after the activated carbon water filter made from oil palm waste. This is the conversion of agricultural waste into value-added product. Conventional steps were performed to produce the activated carbon where the EFB undergoes a pyrolysis process (pre- treatment), carbonization and activation before being utilized as water filter. A turbidity test was conducted to observe the potential of the activated carbon to filter the murky water. The findingsshow that the activated carbon from palm oil waste indeed has the potential to absorb impurities from the murky water. Further analysis can improve the abilities of the activated carbon oil palm-based waste as a water filter.